(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Many endothelial capillary cells are damaged under these conditions, including those in the retina, renal glomerulus, and both central and peripheral nerves, due to excessive harmful accumulation of glucose in these cells. Elevated blood glucose levels or HG increase aldose reductase activity that converts glucose to sorbitol. Intracellular sorbitol accumulation increases cellular osmotic injury, and exaggerates oxidative stress. Sorbitol dehydrogenase eventually converts sorbitol to fructose. During prolonged increases in blood glucose levels, the PKC pathway is an added element in diabetic complications. Hyperglycaemia induces the production of diacylglycerol, which promotes activation of the PKC pathway. People with mild and severe chronic DM have to comply with daily intake of hypoglycemic drugs, including insulin, and they must also exercise every day. Adherence to both non-pharmacological and pharmacological treatments, as well as knowledge about DM can definitely improve the quality of life of diabetic patients.